Pelayanan dan Fasilitas Pendukung Wisata Religi di Masjid Agung Kota Medan Sumatera Utara: Analisis Kualitatif terhadap Pengalaman Pengunjung - Auliya Habibullah; Fadilla Ayuningtrias; Nurheprina Sari Tambunan; Rafli Abdul Bahri; Shafwan Shauri Nst; Sri Windari (Polyscopia, 2026)
The rapid growth of religious tourism in Indonesia has increased the importance of improving service quality and supporting facilities at major religious destinations. This study examines the quality of services and supporting tourism facilities at the Great Mosque of Medan, North Sumatra, while exploring visitors' experiences and perceptions of the services provided. A descriptive qualitative approach was employed, with data collected through field observations, in-depth interviews with eight informants, and documentation. The data were analyzed using the Miles and Huberman interactive model, encompassing data reduction, data display, and conclusion drawing, while source triangulation was applied to ensure the credibility of the findings. The results reveal that the overall quality of services at the Great Mosque of Medan is satisfactory, particularly in terms of the hospitality of the management and the cleanliness of the mosque environment. Nevertheless, several supporting facilities, including parking areas, accessibility for visitors with disabilities, and the availability of comprehensive tourism information, remain inadequate and require further improvement. Visitors also expressed expectations for more informative facilities and a better-organized tourism experience. These findings suggest that enhancing service quality and supporting infrastructure is essential for strengthening visitor satisfaction and optimizing the Great Mosque of Medan as a sustainable religious tourism destination.